Faktor-Faktor Yang Mempengaruhi Kualitas Prosedur Pengendalian Internal Dan Perannya Dalam Memoderasi Hubungan Persepsi Keadilan Organisasi Terhadap Employee Fraud - Ika Hariyanti (Universitas Muhammadiyah Semarang, 2020)
This research aims to analyze the perception of organizational justice on employeefraud moderated by the quality of the internal control procedures of manufacturecompany in Semarang. The factors which affect the quality of internal controlprocedures is ethical corporate environment, risk management training, internalaudit activities, suitability compensation and power leadership. The population ofthis research is the top management level at the manufacture company in Semarang.The sampling technique is random sampling. 32 samples used in this research andOLS regression analysis with SPSS 19 version program. The results of this researchverify that quality of internal control procedures positively moderate the relationbetween perception of organizational justice and employee fraud. Ethical corporateenvironment and risk management training has a positive and not significant to thequality of internal control procedures. Internal audit activities has positive andsignificant to the quality of internal control procedures. Suitability compensationand power leadership has a negative and significant to the quality of interna controlprocedures.